Connections between Africa and Crete in the Late Roman and Proto-Byzantine periods attested in the South Building at Gortyna - Perna, Roberto (Rei Cretariae Romanae Fautorum Acta, 2022)
This paper analyses material evidence from recent archaeological excavations of the South Building of the Byzantine Houses District at Gortyna. For the period under exam the presence of goods of African provenance testifies to a constant flow and trade relations between the two geographical areas, despite the significant variations over time.